A skills beyond school review of Switzerland - Fazekas, Mihály [Verfasser]; Field, Simon [Verfasser] (OECD Publishing, 2013)
Der Report 'A Skills beyond School: Review of Switzerland' analysiert die Situation der höheren Berufsbildung in der Schweiz: Dem Report zufolge ist das Berufsbildungssystem eine solide Grundlage für die berufliche Höherqualifizierung und Weiterentwicklung. Ferner seien Lehrbetriebe gut in das System eingebunden und die Berufsqualifikationen würden von der Wirtschaft geschätzt. Der Bericht empfiehlt abschließend folgende Maßnahmen: "Informationen zu Qualität und Kosten verbessern; den Wechsel aus der beruflichen Grundbildung und höheren Berufsbildung in die Hochschulbildung erleichtern; die internationale Vernetzung verbessern; Berufsfachschulen sollten ein größeres Gewicht auf Rechen- und Lesefähigkeiten legen; ein neues interkantonales Finanzierungsabkommen realisieren." (Textauszug; BIBB-Doku)

This review is one of a series of country reports on postsecondary vocational education and training (VET) in OECD countries. The series includes reviews (such as this one), involving an in-depth analysis of a country system leading to a set of policy recommendations backed by analysis. The structure of this report is as follows: This first chapter places the review of Switzerland in the context of the wider OECD study, presents the structure of the report, describes the main features of the Swiss postsecondary VET system, and compares its main features with those of other countries. It also sets out a number of key statistical indicators comparing Switzerland with other OECD countries. Chapters 2-6 advance policy recommendations, refering to: "Ensuring finance is no barrier to professional education and training" (chapter 2); "Making the market work better – inter-cantonal financing arrangements" (chapter 3); "Making the professional education and training (PET) market work better – transparency and quality" (chapter 4); "Responding to globalisation and technological change" (chapter 5); "Improving numeracy and literacy skills" (chapter 6). (BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildung; Durchlässigkeit im Bildungssystem; Finanzierung; Schweiz